Dari Mianzi Dan Lian Menuju Face: Dari Kearifan Lokal Cina Menuju Teori Kesantunan Yang Mendunia - Pramujiono, Agung (Lingua Cultura, 2012)
The politeness theory of Brown and Levinson (1987) about face is regarded as one veryÂ influential. In fact, it was rooted from Eastern local wisdom (ancient China), that is â€œmianziâ€ andÂ â€œlianâ€. Mianzi represents social perceptions of oneâ€™s self-esteem built through lian as oneâ€™s morality.Â Politeness and limao have the same pragmatic basis but they can be perceived differently due to theÂ varied cultural contexts underlying a speech community. In the intercultural pragmatics study, theÂ differences should not form the sources of conflict but they should even be considered as varieties ofÂ pluralities about which the interactants should be understood in order that interpersonalÂ communication activities can run harmoniously and can be avoided from all kinds of conflict andÂ friction.